2008
DOI: 10.1002/ijc.23571
|View full text |Cite
|
Sign up to set email alerts
|

Risk of gastric cancer in asymptomatic, middle‐aged Japanese subjects based on serum pepsinogen and Helicobacter pylori antibody levels

Abstract: A total of 5,209 asymptomatic, middle-aged subjects, whose serum pepsinogen (PG) and Helicobacter pylori antibody levels had been assessed, were followed for 10 years. Subjects with positive serum H. pylori antibodies (>50 U/mL) had an increased cancer risk (HR 5 3.48, 95% CI 5 1.26-9.64). Risk of gastric cancer increased as the antibody level increased; the H. pylori-positive group with antibody levels >500 U/mL had the highest incidence rate (325/100,000 person-years). Cancer development also increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 57 publications
6
74
2
Order By: Relevance
“…In particular, the group with Hp-CSA-/CagA+, compared with the reference group seronegative with both tests, has an odds ratio as high as 68.0. This is consistent with a recent Japanese cohort study among middle-aged subjects [23]. There, a more than 100-fold excess risk of stomach cancer was noted in the group seronegative with H. pylori antibodies but with a low pepsinogen I:II ratio.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the group with Hp-CSA-/CagA+, compared with the reference group seronegative with both tests, has an odds ratio as high as 68.0. This is consistent with a recent Japanese cohort study among middle-aged subjects [23]. There, a more than 100-fold excess risk of stomach cancer was noted in the group seronegative with H. pylori antibodies but with a low pepsinogen I:II ratio.…”
Section: Discussionsupporting
confidence: 92%
“…Subjects were divided into three groups according to PG II level: group II-0, PG II B10 ng/ml; group II-10, PG II [10 ng/ml and B30 ng/ml; group II-30, PG II [30 ng/ml. These thresholds were determined in a previous study according to the risk of gastric cancer [13].…”
Section: Serologic Analysismentioning
confidence: 99%
“…In contrast, correlations between activity of gastritis and altered mucosal DNA methylation levels have not been reported. Activity of gastritis is reportedly correlated with the development of diffuse-type gastric cancer [10,13]. We therefore hypothesized that the degree of altered DNA methylation in stomach mucosae is correlated with activity of gastritis, since methylation observed in inflammatory stomach mucosae would directly or indirectly induce diffuse-type cancer development.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have reported that, besides progression of gastric mucosal atrophy, patients with severe gastric mucosal inflammation (high PG-II levels and/or high H. pylori antibody titers) are at high risk for gastric cancer, particularly diffuse-type carcinoma (Yanaoka et al, 2008b), and that in these patients H. pylori eradication may likely prevent gastric cancer (Yanaoka et al, 2009). In this study, the high-intake group had significantly lower H. pylori antibody titers and lower serum PG-II, suggesting that JA intake may be effective in preventing gastric cancer whose mechanism involves H. pylori-related active mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%